2021
DOI: 10.1037/ccp0000683
|View full text |Cite
|
Sign up to set email alerts
|

Change in negative attention bias mediates the association between attention bias modification training and depression symptom improvement.

Abstract: Objective: Attention bias modification training (ABMT) is purported to reduce depression by targeting and modifying an attentional bias for sadness-related stimuli. However, few tests of this hypothesis have been completed. Method: The present study examined whether change in attentional bias mediated a previously reported association between ABMT condition (active ABMT, sham ABMT, assessments only; N = 145) and depression symptom change among depressed adults. The preregistered, primary measure of attention b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 53 publications
(99 reference statements)
1
1
0
Order By: Relevance
“…First, this study identified evidence of enhanced disengagement ability from negative stimuli following ABM. Given the association between the dwell time on negative stimuli and the severity of depression shown in the previous study (Beevers et al, 2021 ), the results of this study could be interpreted as supporting the effectiveness of ABM. However, considering that the reduction of depressive symptoms after ABM was not verified, this study could not indicate that ABM has a direct effect on reducing depressive symptoms.…”
Section: Limitationssupporting
confidence: 74%
“…First, this study identified evidence of enhanced disengagement ability from negative stimuli following ABM. Given the association between the dwell time on negative stimuli and the severity of depression shown in the previous study (Beevers et al, 2021 ), the results of this study could be interpreted as supporting the effectiveness of ABM. However, considering that the reduction of depressive symptoms after ABM was not verified, this study could not indicate that ABM has a direct effect on reducing depressive symptoms.…”
Section: Limitationssupporting
confidence: 74%
“…This convergent pattern of results might be explained by how CBT + ABM helped patients with PD to reallocate attention resources toward neutral material while simultaneously avoiding negative cues. Other mechanisms that merit testing by future empirical studies include reduced attention to upsetting material, negative interpretations and repetitive thinking (e.g., ruminative brooding), increased frequency of positivity bias, and altered brain regions implicated for emotion regulation (Beevers, Clasen, Enock, & Schnyer, 2015; Beevers, Hsu, Schnyer, Smits, & Shumake, 2021; Van Bockstaele et al ., 2019). For example, mounting neuroimaging and eye tracking–based evidence (e.g., Li et al ., 2016; Mobius, Ferrari, van den Bergh, Becker, & Rinck, 2018) indicates that ABM could facilitate disengagement from threat and modify reward‐ and executive functioning–related regions.…”
Section: Discussionmentioning
confidence: 99%